COVID-19 PNEUMONIA ASSOCIATED WITH RHABDOMYOLYSIS IN PATIENT WITH PREVIOUS CHRONIC THERAPY WITH STATIN: COINCIDENCE OR REALTED CONDITIONS? - Kartalova, Marija Janeku; Cvetanovska, Marija; Stevanovic, Milena; Demiri, Ilir; Bogoeva, Sunchica Taseva; Cvetanovski, Vlatko (Journal of Morphological Sciences, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus which causes coronavirus disease 2019 (COVID-19). It was first identified amid an outbrake of respiratory illness cases in Wuhan City, Hubei Province, China. COVID-19 was reported to the world Health Organisation (WHO) on 31 December 2019 and declare as a global pandemic on 11 March 2020 . Presentation of COVID-19 range from asymptomatic or mild symptoms to severe illness or death. The most serious complication of COVID-19 is a type of pneumonia thatâ€™s been called 2019 novel coronavirus-infected pneumonia (NCIP). COVID-19 pneumonia presents as an atypical pneumonia, with diffuse bilateral lung involvement. Severe cases present with acute lung injury, and acute respiratory distress syndrome (ARDS). Rhabdomyolisis can be initial presentation of COVID-19, and also is a life-threatening disorder. Rhabdomyolysis is the breakdown of skeletal muscle by releasing it cellular content into the systemic circulation.  A 73-year-old man was admitted to our hospital with bilateral pneumonia, muscle pain, and worsening symptoms. On hospital day 5 his oxygen saturation get low, so we started treatment with oxygen inhalation by high flow mask. On the 14th hospital day the muscle enzymes started increasing. After propriety treatment the patient was discharged on hospital day 28.Patient with COVID-19 pneumonia can developed rhabdomyolysis because of SARS CoV-2 infection also there is a risk of developing rhabdomyolysis after using drug for treatment of COVID-19. Our patient was on previous chronic therapy with statins but with normal liver and muscle enzymes. During his hospitalization and deteriorated of his clinical condition the enzymes increased with presentation of rhabdomyolysis. Our findings indicate that rapid clinical recognition and positive hydration treatment of COVID-19â€“asociated rhabdomyolysis can reduce the risk for serious complications. Keywords :  SARS-CoV-2, COVID-19, COVID-19 pneumonia, rhabdomyolysis, chronic statin therapy https://doi.org/10.55302/JMS2141006jk